Energy saving in the enterprises of fuel and energy complex textbook/учебное пособие - Ushakov, V. Ya. specialist in the field of electric power engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences 1939- (TPU Publishing House, 2017)
The textbook focuses on the analysis of the energy efficiency of the main enterprises of the fuel and energy complex (FEC) of the countries with a high level of development of the power engineering. Given analysis of the reasons of losses energy resources and electricity, the energy saving potential and methods its evaluation and the implementation in the production, transmission and distribution of electricity and heat. It is addressed to foreign undergraduates and bachelors, students in the direction of "Power engineering", as well as to Russian graduate students, who had mastered a English language or is mastering of it, for researchers and professionals dealing with the problems of energy saving and energy efficiency.